Beyond The Circle: The Spread of Imm Cadres Across Student Organizations in Muhammadiyah Universities - Mahasri Shobahiya; Putri Rahmawati; Fauziyah Qurrota’Ayun Tamami; Zulfa Iftinani Muchtar; Mirzam Arqy Ahmadi (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study critically examines the role of the Muhammadiyah Student Association (Ikatan Mahasiswa Muhammadiyah—IMM) in preparing functional cadres for student organizations (Ormawa) at Universitas Muhammadiyah Surakarta (UMS). As an autonomous student wing of Muhammadiyah, IMM holds a strategic mandate in leadership development—not only for its internal structure but also to support the broader ecosystem of student leadership within the university. Employing a descriptive approach with a mixed-methods design, the study integrates basic quantitative analysis through percentage-based calculations and qualitative analysis using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. Data were collected through in-depth interviews and document analysis. The findings reveal that in 2022, IMM’s contribution to the formation of functional cadres in Ormawa accounted for only 4% of the total leadership demand, indicating a significant gap between the organization’s idealized role and its actual implementation. Key challenges identified include low student participation in the Darul Arqam Dasar (DAD) training program and insufficient cadre readiness in terms of ideological understanding and leadership capacity. The study recommends a comprehensive strengthening of cadre development strategies—both in quality and quantity—to enhance IMM’s contribution to student leadership sustainability at UMS